On the Opposing Nature of Novella in the Legislative Regulation of the Investigatory Action "Arrest Of Postal And Telegraph" - Suprun, Sergei; Cherkasov, Viktor (Sibirskoe ûridičeskoe obozrenie (Online), 2017)
The article analyzes the legislative innovation relating to the investigative action “arrest of postal and telegraph dispatches, their inspection and seizure” and associated with the ability to seize and inspect electronic and other messages transmitted via telecommunication networks. The Authors conclude that these novellas do not agree with the subject, the form of investigative action “arrest of postal and telegraph dispatches, their inspection and seizure" and contrary to the normative legal acts regulating public relations in the field of electronic information.